La peligrosa híper-constitucionalización del Derecho: análisis preliminar del caso peruano - Monge Morales, Gonzalo J. (2025)
This article provides a preliminary analysis, intended to generate academic debate, of the hyper-constitutionalization of Law in Peru, a littlestudied but highly relevant topic of contemporary relevance.If everything is constitutionalized, excesses can be committed. If everything is constitutional, then nothing is. And although contemporary constitutions and the constitutionalism of rights offer merit, the misunderstood constitutionalization of Law can lead to dangers that jeopardize what it was promised to protect: fundamental rights.